In Vivo Uricosuric Effect of Red Betel Leaves (Piper crocatum RUIZ & PAV) Ethanol Extract - Hermanto, Faizal; Wahyuningsih, Sri (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2024)
Hyperuricemia a condition where a person has high levels of uric acid in the blood. Red betel (Piper crocatum RUIZ & PAV) is a plant empirically used to reduce uric acid levels. This study aimed to determine the effective dose of red betel plant in reducing urinary uric acid levels in male Wistar rats with hyperuricemia. Hyperuricemia condition was obtained by giving chicken liver juice 25 mL/kg orally and potassium oxonate 250 mg/kg intraperitoneally. Red betel extract (RBE) is made by maceration using 50% ethanol. Male Wistar rats were divided into five groups: negative control (CMC-Na 0.5%), Positive control (Probenecid 4, 5 mg/kg), and extract at doses 11.5, 23 and 46 mg/kg. The results showed that the RBE increased uric acid secretion through urine (uricosuric) compared to controls. The optimal dose for the uricosuric effect of the extract is 46 mg/kg, although this effect is lower than probenecid. Keywords: Red betel, uric acid, potassium oxonate, uricosuric